2021
DOI: 10.5468/ogs.21178
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes of tension-free vaginal tape (TVT)- abbrevo® and TVT-obturator® for the treatment of stress urinary incontinence: a retrospective study

Abstract: ObjectiveWe compared the efficacy and postoperative complications of tension-free vaginal tape (TVT)-abbrevo® (TVT-A) and TVT-obturator® (TVT-O) surgeries for the treatment of stress urinary incontinence (SUI).MethodsWe retrospectively analyzed the medical records of 143 female patients with SUI who underwent TVT-A or TVT-O surgery between January 2010 and December 2019 at the Asan Medical Center in Seoul. We evaluated intra- and postoperative complications such as bladder injury, groin pain, urinary retention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Relevant research shows that TOT operation time is only 1/2 of TVT operation time, but the surgical cure rate of both is similar [ 10 ], so more and more operators choose TOT to treat stress urinary incontinence. However, the number of patients with simple urinary incontinence without pelvic organ prolapse in clinical observation is relatively small, and the effect of only using a middle sling to treat SUI is not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant research shows that TOT operation time is only 1/2 of TVT operation time, but the surgical cure rate of both is similar [ 10 ], so more and more operators choose TOT to treat stress urinary incontinence. However, the number of patients with simple urinary incontinence without pelvic organ prolapse in clinical observation is relatively small, and the effect of only using a middle sling to treat SUI is not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the neurotoxic consequences of paclitaxel, it is possible that the urinary system may be affected, resulting in micturition symptoms such as urinary incontinence. This could potentially disturb the quality of life and possibly require surgical correction [ 12 ]. The present study revealed that though the PT regimen might worsen urinary incontinence in gynecologic patients, the symptoms were mild and transient.…”
Section: Discussionmentioning
confidence: 99%
“…TVT-A is one of the newest MUS devices for the treatment of SUIs, introduced by Waltregny et al [ 6 ]. Several studies have produced extremely encouraging results at short-term evaluation [ 22 , 23 , 24 ]; however, only a few studies in the literature have assessed the medium-long term durability and safety of this surgical procedure.…”
Section: Discussionmentioning
confidence: 99%